2018
DOI: 10.1016/j.pbb.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Late aging alters behavioral sensitivity to ethanol in a sex-specific manner in Fischer 344 rats

Abstract: Responsiveness to ethanol (EtOH) differs as a function of age. Adolescent rodents are less sensitive than adults to the sedative effects of EtOH, whereas they show enhanced sensitivity to EtOH-induced social facilitation. Late aging is associated with a natural decline in social behavior and aging-related peculiarities in sensitivity to EtOH have been largely unexplored. Whether there are sex differences in the behavioral response to EtOH during late aging remains unknown. Thus, behavioral responses to EtOH in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…One of the few studies to address sex differences in alcohol effects in older animals looked at social interaction, as well as ethanol sensitivity as a function of age and sex, by examining latency and duration of the loss of righting reflex (LORR) following i.p. injection of ethanol [86]. In adult males and females, injection of 0.5 or 0.75 g/kg of ethanol decreased social behavior.…”
Section: Behavioral and Functional Effectsmentioning
confidence: 90%
“…One of the few studies to address sex differences in alcohol effects in older animals looked at social interaction, as well as ethanol sensitivity as a function of age and sex, by examining latency and duration of the loss of righting reflex (LORR) following i.p. injection of ethanol [86]. In adult males and females, injection of 0.5 or 0.75 g/kg of ethanol decreased social behavior.…”
Section: Behavioral and Functional Effectsmentioning
confidence: 90%
“…Regarding studies in animal models, the main effects of alcohol that have been evaluated are cognition, ataxia, hypothermia, and sedation. In the latter three, an age-dependent increase was observed when comparing adolescent, adult, and aged animals ( Matthews et al, 2019 ; Ornelas, Novier, Van Skike, Diaz-Granados, & Matthews, 2015 ; Perkins, Vore, Lovelock, Varlinskaya, & Deak, 2018 ; Silveri & Spear, 2000 ; Van Skike et al, 2010 ; Watson, James, Mittleman, & Matthews, 2020 ). In studies where the effects on cognition were tested, specifically spatial memory tests, no differences were observed between adolescent and adult animals following an acute dose of alcohol ( Chin et al, 2011 ; Matthews, Scaletty, Schreiber, & Trapp, 2020 ); however, aged animals did show impairment on memory tasks in general, both those assessing spatial and non-spatial memory ( Matthews et al, 2020 ).…”
Section: Alcohol Abuse Disorders and Agingmentioning
confidence: 93%
“…Furthermore, sex differences in the behavioral response to ethanol were observed in aged rats. For instance, aged females, but not males, exhibited social facilitation after intraperitoneal injection of low doses of ethanol ( Perkins et al, 2018 ). However, there are no available data demonstrating sex differences in alcohol intake in older animals and even less about underlying mechanisms.…”
Section: Main Neurotransmitters Affected By Agingmentioning
confidence: 99%
“…Alcohol use has been high or rising in most demographics including adolescents, young adults, and older females without children . However, compared to younger drinkers, the percentage of older adult drinkers has had a greater escalation in recent years, and older adults often consume alcohol in a hazardous binge drinking pattern. Recent preclinical research has demonstrated that aged rodents are more sensitive to the effects of acute ethanol exposure compared to younger adult rodents. Furthermore, chronic intermittent ethanol exposure (CIEE), a model of binge-like ethanol consumption, may produce tolerance to a high-dose ethanol challenge in aged animals faster than in younger adult animals and impair cognition late in life. , Given the increases in the percentages of drinkers and the engagement of more hazardous consumption patterns in the aged population, understanding the potential negative impacts of alcohol on the aged is critical.…”
Section: Introductionmentioning
confidence: 99%
“… 10 14 Recent preclinical research has demonstrated that aged rodents are more sensitive to the effects of acute ethanol exposure compared to younger adult rodents. 15 20 Furthermore, chronic intermittent ethanol exposure (CIEE), a model of binge-like ethanol consumption, may produce tolerance to a high-dose ethanol challenge in aged animals faster than in younger adult animals 21 and impair cognition late in life. 15 , 22 Given the increases in the percentages of drinkers and the engagement of more hazardous consumption patterns in the aged population, understanding the potential negative impacts of alcohol on the aged is critical.…”
Section: Introductionmentioning
confidence: 99%